PENGARUH PENGERINGAN TERHADAP DAYA HIDUP DAN INTENSITAS SERANGAN BUBUK KAYU KERING HETEROBOSTRYCHUS AEQUALIS WAT PADA KAYU PULAI (ALSTONIA SCHOLARIS R.Br) - Ginuk Sumarni; Jasni Jasni (Jurnal Penelitian Hasil Hutan, 1989)
Heterobostrychus aequalis  Wat is very  important   wood  destroying   insect  other  than  termites.  In  this experiment pulai  wood  samples  (Alstonia  scholaris  R.Br)  taken  from  above  and  under  a girdle  of  cut  around  tree stem  were dried at temperature   40˚C,  60˚C,  90°C,   100°c,    120°c,    150°C, 200°c    and  air  temperature.   On  each  side  of  the  samples  of 1,5  cm  x  5  cm  x  7 cm.  Into   in  dimension   ten  holes  were  made  the  hole  larvaes of  1,5  month   old  were  placed.   The observations  were  made after  six  week  period.Wood dried at  temperature  40°C  had the lowest starch content  i.e 13,40  % for wood  samples  the girdle and 11,15  % for  wood  samples  under  the  girdle,  white   the  intensity   of  insect's  attack   can  be  rated  os moderate   (with  score  67,25 and  65,75).